Nothing about Us without Us: Inclusion and IRB Review of Mental Health Research Protocols. Issue 3 (11th May 2022) - Tully, Ian
ABSTRACT: Research on mental health and illness presents a variety of unique ethical challenges. This article argues that institutional review boards (IRBs) can improve their reviews of such research by including the perspectives of individuals with the condition under study either as members of the IRB or as consultants thereto. Several reasons for including the perspectives of these individuals are advanced, with the discussion organized around a hypothetical case study involving the assessment of a novel talk‐therapy modality. Having made this case, the article goes on to explain how to implement the idea by building on a recent proposal by Rebecca Dresser, who argues in a number of publications for the inclusion of former research participants in the IRB review process. Finally, concerns about protecting reviewer and consultant confidentiality are addressed.